Decolonizing African Studies. Issue 3 (1st September 2020) - Kessi, Shose; Marks, Zoe; Ramugondo, Elelwani
Abstract : In this introduction to the special issue on decolonizing African Studies, we discuss some of the epicolonial dynamics that characterize much of higher education and knowledge production in, of, with, and for Africa. Decolonizing, we argue, is best understood as a verb that entails a political and normative ethic and practice of resistance and intentional undoing – unlearning and dismantling unjust practices, assumptions, and institutions – as well as persistent positive action to create and build alternative spaces and ways of knowing. We present four dimesions of decolonizing work: structural, epistemic, personal, and relational, which are entangled and equally necessary. We offer the Black Academic Caucus at the University of Cape Town as an example of how these dimensions can come to life, and introduce the contributions in this special issue (the first of a two-part series) that illuminate other sites and dimensions of decolonizing.